ASSESSING THE ADOPTION OF CONSERVATION AGRICULTURE TOWARDS CLIMATE CHANGE ADAPTATION: A CASE OF NKOMAZI, MPUMALANGA PROVINCE - Sithole, Moses Zakhele; Agholor, Azikiwe Isaac (Proceedings of the International Conference on Agriculture, 2022)
Climate change is a threat to agricultural productivity and the overwhelming effects of climate change hinders the quest for sustainable agriculture, with the aim of satisfying the increasing demands for food and fiber. Adaptation to the ever-changing climate is a necessity for the agricultural sector. The study was conducted in Nkomazi Local Municipality. The study assessed the adoption of conservation agriculture in relation to climate change by smallholder farmers. Focus group discussion, structured and semi-structured questionnaires were used to randomly collect data from selected smallholder farmers. The data was analyzed using the binary logistics regression model to determine adoption behavior of farmers in the use of conservation agriculture. Logistic regression result show that several predictor variables were found to significantly influence the adoption behavior of smallholder farmers in the area. The study noted the existence of significant variables to include age, education, household size, income, number of children, and adoption of conservation agricultural practice. Marital status of the farmers was found not to be significant and never to influence the adoption behavior of farmers with a p-value of (0.911) and co-efficient of (0.102). Furthermore, thoughtful decision process and smallholder farmers’ capacity development and training on conservation techniques must be accentuated. It is therefore, recommended that future research be undertaken on the extent to which the effects of climate change affect farmer’s productivity as well as the lack of youth involvement in agricultural production in the study area.